RECURRENT HYPOGLYCEMIA IN A TEENAGER WITH OBESITY: A CASE REPORT - MF, Lee Ryan; Suria, Mas; KG, Goh; MA, Md Syazwan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
IINTRODUCTION Reactive hypoglycaemia is a condition of postprandial hypoglycemia occurring within 2 to 5 hours after meal intake. This condition is characterised by inappropriately increased blood insulin levels due to pancreatic overactivity to carbohydrates, most often refined sugars, thus producing hypoglycaemic symptoms. Recent studies have shown that the prevalence of T2D in obese children and adolescents is 0.18–7.9%, which is five times that in normalweight individuals. CASE This is a case of a 16-year-old female with a BMI of 34.28 kg/m2 who presented with frequent symptoms of hypoglycaemia, mainly palpitations, sweating, giddiness and syncopal attacks since January 2023. The frequency of symptoms was noted 5 to 6 times per week, commonly occurring 4 hours post-meal and after strenuous activity. She practices a heavy dietary intake 4 times per day with refined carbohydrates at each meal. Clinically, the patient exhibits signs of insulin resistance such as acanthosis nigricans. She underwent a mixed-meal tolerance test in November 2023 which showed no clinical and biochemical evidence of hypoglycaemia. Following that, continuous glucose monitoring was arranged for a week which showed hypoglycaemic episodes ranging from 3.5 to 3.9 mmol/L in the afternoon of one of the days. She was prescribed Acarbose but declined treatment due to gastrointestinal intolerance. She opted for a high fibre, low glycaemic index diet with frequent small meals which showed improvement of the symptoms. CONCLUSION Lifestyle modifications are the mainstay of management and prevention of the development of diabetes mellitus for patients with reactive hypoglycaemia. Furthermore, studies have shown that the addition of metformin or acarbose also plays a vital value in preventing reactive hypoglycaemia.